8-Week Basic Military Training Improves Adiponectin Multimer Ratio in Healthy Young Males - Han, Xinjun; Feng, Yan; Han, Xinbing; Guo, Haiqing; Zhu, Jianbo; Ning, Chao; Liu, Fen; Li, Shidong; Li, Xiaomei; Yang, Yi-ning (International Journal of Sports Medicine, 2019)
To investigate the effect of exercise on adiponectin in young healthy human males, we examined serum total adiponectin and high-molecular-weight (HMW) adiponectin in newly recruited male soldiers who participated in an 8-week basic military training (BMT). A total of 95 males (mean age, 18.79±1.50 years) were sampled from among 1,100 new male army recruits in China. Participants were separated into 3 groups according to their body mass index (BMI): overweight group (BMI: 24.9 kg/m2 to<30 kg/m2; n=26); normal-weight group (BMI: 18.5 kg/m2 to<24.9 kg/m2; n=40); and underweight group (BMI:<18.5 kg/m2; n=29). Anthropometric measurements, fasting serum total adiponectin, HMW adiponectin, and lipid profiles were recorded at baseline and at the end of the 8-week BMT. After the 8-week BMT, the HMW/total adiponectin ratio (HMW/total ratio) and HDL cholesterol improved significantly (p<0.001 and p<0.001, respectively). HMW/total ratio showed significant correlations with HDL cholesterol. Our study suggests that an 8-week BMT can improve the HMW/total ratio in healthy young males regardless of their BMI and anthropometry. Both HMW/total ratio and HDL cholesterol can serve as potential biomarkers for assessing the efficacy of exercise and may have metabolic benefits for preventing obesity and obesity-related disease.
Keywords: healthy young male; exercise; adiponectin; HMW adiponectin; lipid profile; HDL cholesterol